Exchange Rates and Export Structure - HSU, Wen-Tai (Institutional Knowledge at Singapore Management University, 2014)
This paper studies whether changes in the exchange rate affect a country’s export structure, using an arguably exogenous sudden appreciation of renminbi on July 21, 2005 as the main source of identification. Employing combined regression discontinuity and difference-in-differences approach, we show that China’s export structure became more similar to that of the developed countries after the currency appreciation. We also find that the majority of the appreciation effect comes from the inter-firm resource reallocation rather than the inter-region or intra-firm resource reallocation.